Electromagnetic High Frequency Gyrokinetic Particle-in-Cell Simulation (Communications in Computational Physics, 2008)
Using the gyrocenter-gauge kinetic theory, an electromagnetic version ofthe high frequency gyrokinetic numerical algorithm for particle-in-cell simulation hasbeen developed. The new algorithm, being an alternative to a direct Lorentz-forcesimulation, offers an efficient way to simulate the dynamics of plasma heating andcurrent drive with radio frequency waves. Gyrokinetic formalism enables separationof gyrocenter and gyrophase motions of a particle in a strong magnetic field. Fromthis point of view, a particle may be viewed as a combination of a slow gyrocenter anda quickly changing Kruskal ring. In this approach, the nonlinear dynamics of highfrequency waves is described by the evolution of Kruskal rings based on first principles physics. The efficiency of the algorithm is due to the fact that the simulationparticles are advanced along the slow gyrocenter orbits, while the Kruskal rings capture fast gyrophase physics. Moreover, the gyrokinetic formalism allows separationof the cold response from kinetic effects in the current, which allows one to use muchsmaller number of particles than what is required by a direct Lorentz-force simulation.Also, the new algorithm offers the possibility to have particle refinement together withmesh refinement, when necessary. To illustrate the new algorithm, a simulation ofthe electromagnetic low-hybrid wave propagating in inhomogeneous magnetic fieldis presented.